The importance of facilitation in successful adaptation - Kazanzhy, Mariia (My University, 2017)
This paper presents the data concerning the connectedness of the facilitative potential components, its manifestation in different fields of vital activity, basic senses of helping behaviour and socio-psychological adaptability. Based on the results of multiple regressive analysis, there has been established the importance of all facilitation aspects in order to predict personality adaptability. It has been proved that persons with developed facilitation have a higher degree of adaptability (on the sample of socionomic professions). The study of the peculiarities of adaptation directly in a complex life situation which is the process of accommodation to a foreign environment that can be combined with the beginning of family relations and is a rather tense and difficult period in subjects’ lives has shown the importance of the facilitative ability in the success of its course. The obtained data provide valuable information on possible ways to increase the individual adaptivity through the development, formation of their facilitative potential, as well as the facilitative qualities of the social environment.
Kazanzhy M. Y. The importance of facilitation in successful adaptation / M. Y. Kazanzhy // Science and Education. - 2017. - Issue 7 . - P. 142-146.
Keywords: facilitative ability; facilitative potential; sense motivation of help; fields of facilitation; adaptation; socio-psychological adaptability